Treadmill Hand Injuries Among Children: A Retrospective Case Series From Hospitalized Patients - Zhang, Yunxuan; Liu, Yan; Yuan, Xingang; Xiao, Jun; Ding, Xionghui; Chen, Qiang; Qiu, Lin (Frontiers in Pediatrics, 2021)
Background: With the progress of modernization, treadmill hand injury in pediatric population is taking on a global trend in recent years. The purpose of this study was to investigate the epidemiology and clinical features in a developing country, thereby providing some experience in the treatment and prevention of this particular type of injury. Methods: A five-year retrospective review of patients with treadmill hand injury in Burn and Plastic Surgery ward at Children’ Hospital of Chongqing Medical University was conducted. Demographics, injury details, therapy performed, length of hospital stay, complications, and outcome were analyzed. Results: Forty-six patients were surveyed, with a mean age of 3.5±2.0 years old, including 24 males and 22 females. Seventy-seven point eight percent of injuries occurred between dinner to bedtime, and 95.7% happened indoors. Fingers were the most vulnerable part, of which the middle finger, ring finger and index finger were the top three ones. The mean body surface area (BSA%) was 0.3±0.2, but at least in deep dermal. Dressing changes, full-thickness skin grafts (FTSG), and Negative Pleasure Wound Therapy (NPWT) assisted FTSG were performed. The scar contracture, as the most severe complication, occurred in 26 patients, of which 22 originally received dressing changes at the time of injury. Conclusion: Treadmill hand injury in children should be highly regarded. Compared with conservative dressing changes, surgical intervention from a professional team may achieve more satisfactory prognosis and fewer complications. A prevention strategy based on “Time-Space-Person” was summarized according to its epidemiological characteristics, may help to decrease the incidence of this specific type of injury theoretically.